PENGARUH KONSUMSI TABLET TAMBAH DARAH (TTD) DENGAN AIR JERUK LEMON TERHADAP KADAR HEMOGLOBIN PADA REMAJA PUTRI DI SMK dr. Soebandi Jember : PENGARUH KONSUMSI TABLET TAMBAH DARAH (TTD) DENGAN AIR JERUK LEMON TERHADAP KADAR HEMOGLOBIN PADA REMAJA PUTRI DI SMK dr. Soebandi Jember - Anggraeni, Ernawati; Yuningsih (LPPM STIKes Bahrul Ulum Jombang, 2025)
Background: : Based on data from Riskesdas of Jawa Timur province in 2018, the target of adolescent girls who have received TTD is 24.8% and in the last 12 months as much as 75.4%. In the age group of 12-15 years who get TTD 27.02% and in the last 12 months who get TTD as much as 83.76%. Those who did not spend TTD on the grounds of unpleasant taste and smell were 8.9%, there were 13.0% side effects and those who felt unnecessary as much as 78.1%. For menstrual data adolescent girls based on Riskesdas data in 2018 is 67.90%, while the age of first menstruation (Menarche) with an average age of 12.53. The purpose of this study was to determine the effect of TTD consumption with lemon juice on hemoglobin levels in adolescent girls at SMK dr. Soebandi Jember Method: This research method is pre-experimental design, the population is adolescent girls of SMK dr. Soebandi Jember Sampling technique with purposive sampling as many as 47 people.Results: the results of this study obtained a significant effect of consumption of blood-added tablets with lemon juice on hemoglobin levels in adolescent girls at SMK Dr. Soebandi Jember (p-value = 0.01) with a value of α = 0.05. Conclusion: Based on the results of data analysis using the t test, it was concluded that blood-added tablets with lemon juice are very effective in increasing Hb levels in the blood of adolescent girls.